2019
DOI: 10.3390/ma12081325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protective Coatings for High-Corrosivity Category Atmospheres in Offshore Applications

Abstract: The interest in renewable energies obtained from the resources availed in the ocean has increased during the last few years. However, the harsh atmospheric conditions in marine environments is a major drawback in the design of offshore structures. The protective systems that are employed to preserve offshore steel structures are regulated by several standards (ISO 12944, NORSOK M-501), which classify the corrosivity category of offshore installations as C5-M and Im2. In this work, three coatings employed in of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Compared to the corrosion atmosphere of the car body mentioned above, the corrosive environments faced by maritime infrastructures and vessels are more aggressive and severe. There are two serious levels of corrosivity categories for maritime installations: C5-M (Coastal and offshore areas with high salinity) and Im2 (Immersed in sea water) [73,74]. The marine environment is notoriously one of the most corrosive and hostile working atmospheres on metal substrates or other materials.…”
Section: Maritime Infrastructures and Vesselsmentioning
confidence: 99%
“…Compared to the corrosion atmosphere of the car body mentioned above, the corrosive environments faced by maritime infrastructures and vessels are more aggressive and severe. There are two serious levels of corrosivity categories for maritime installations: C5-M (Coastal and offshore areas with high salinity) and Im2 (Immersed in sea water) [73,74]. The marine environment is notoriously one of the most corrosive and hostile working atmospheres on metal substrates or other materials.…”
Section: Maritime Infrastructures and Vesselsmentioning
confidence: 99%
“…-pipeline systems characterized by corrosion damage (Figures 7, 8), due to which the pipe wall becomes thinner and the strength of the system decreases in places of localization of corrosion; -deck mechanisms (cargo devices) -during storms, critical mechanical stresses arise, which lead to breakdowns of the above-described elements and structures of the vessel. The use of the developed materials with improved physical and mechanical characteristics (Table 5) will extend time periods between repairs and protect the surface of these systems from corrosion more effectively (Hou et al 2013;Mouritz et al 2001;Alam et al 2013;López-Ortega et al 2019).…”
Section: Properties Of the Developed And Known Protective Coatingsmentioning
confidence: 99%
“…ISO 2063 and AWS C2.23, mention that the thickness of sealants should not exceed 40 µm. López-Ortega et al [2,50] conducted a series of experiments in which arc-sprayed aluminium with an organic topcoat (epoxydic paint [51]) on high strength, low alloy steel R4 grade was studied. Based on weathering aging tests in different climatic cabinets, as well as immersion tests and tribocorrosion tests in artificial seawater, it was concluded that this duplex system exhibits good corrosion and tribocorrosion properties.…”
Section: Effect Of Sealingmentioning
confidence: 99%
“…The battle against corrosion can be supported in several ways: by appropriate material selection (e.g., corrosion-resistant alloys (CRAs)), by the application of coatings (organic or metallic), by cathodic protection (impressed current or sacrificial anodes), or by the use of corrosion inhibitors and corrosion allowance. The most common corrosion mitigation methods for the protection of offshore structures that are made of steel (usually mild or low-alloyed [2]) involve the application of cathodic protection and/or protective coatings, depending on the conditions to which the structure is subjected. The types of exposure for these materials can be divided into four main zones: atmospheric, splash/tidal, submerged, and buried.…”
Section: Introductionmentioning
confidence: 99%